THE CULTURAL STAGES APPEARS IN EMMELINE IN THE BLUE LAGOON BY RANDAL KLEISER (1980) : PSYCHOSOCIAL PERSPECTIVE - ROSIANA, BETTY (2011)
The purpose of this study is to analyze the psychosocial that is the role culture in relation to the psychosocial stages of Emmeline based on psychosocial perspective in a movie entitle The Blue Lagoon. There are two objectives: the first is to analyze the movie in term of structural elements, and the second one is to analyze the movie based on Psychosocial Perspective . This research is a descriptive qualitative study, using the movie of Randal Kleiser The Blue Lagoon as the object of analysis of the style study. There are two kinds of data sources use in this analyzing, namely primary and secondary. The primary data are the movie itself and the secondary data sources are from the other data, which have relation with the research like psychosocial books and movie script. The technique of data collection in this research is library research by watching the movie, reading books, taking notes for important part, and classifying the data. In analyzing the data, the writer employs descriptive qualitative analysis technique. The result of the research shows that based on the psychosocial Perspective, the stage of life -span development of Emmeline is the believe and faith of her in the unknown God, the law that never exist, the uncontrolled selfish and hope. And, the structural elements which consist of characterization, plot, theme, mise en scene, and cinematography support the entire story and action within the movie.